Characteristics of cutaneous anthrax in Turkey - (:unkn) unknown (J INFECTION DEVELOPING COUNTRIES, 2009)
Background: Incidence of anthrax is diminishing in developed countries; however, it remains a public health problem in developing countries, especially those whose main source of income is farming. Methodology: Charts of patients hospitalized between 1992 and 2008 in the Infectious Diseases and Clinical Microbiology Department of Ankara Numune Education and Research Hospital were reviewed. Results: Fifty-eight cases with cutaneous anthrax were reviewed. The mean age was 49.8, and 36.2% were female. The most common professions were farmers (62%), butchers (19%), and housewives (15%). The mean incubation period was eight days. Most cases (62%) were exposed to bacteria when butchering sick animals. Eighteen patients used an antibiotic before admission to hospital (31%). The predominantly affected sites were hands (39%) and fingers (29%), followed by forearms (12%), eyelids (7%) and necks (3%). All cases initially had painless ulcers with vesicles; dissemination of the lesion was seen in 27.5% of patients. Gram stain was positive in 11 cases; culture was positive in 7 cases for Bacillus anthracis. All patients except one were discharged and treated with penicillin and/or ciprofloxacin or imipenem. One patient with a disseminated lesion on the neck died even though a steroid was used with the antibiotic. Conclusions: Cutaneous anthrax should be considered as a possible diagnosis in cases with a painless ulcer with vesicles, edema, and a history of exposure to animals or animal products. Despite previous antibiotic use, taking smears and cultures should be encouraged. Treatment with penicillin G or penicillin procain alone is effective for cases with cutaneous anthrax without severe edema and superinfection.
Keywords: cutaneous anthrax; Turkey; BACILLUS-ANTHRACIS; ANTIMICROBIAL SUSCEPTIBILITY